Petrogenesis of a hybrid cluster of evolved kimberlites and ultramafic lamprophyres in the Kuusamo Area, Finland - Dalton, Hayden; Giuliani, Andrea; O'Brien, Hugh; Phillips, David; Hergt, Janet; Maas, Roland (Journal of Petrology, 2019)
Kimberlites are often closely associated, both in time and space, with a wide variety of alkaline ultramafic rock types, yet the question of a genetic relationship between these rock types remains uncertain. One locality where these relationships can be studied within the same cluster is the Karelian craton in Finland. In this study we present the first petrographic, mineral and whole-rock geochemical results for the most recently discovered kimberlite cluster on this craton, which represents an example of the close spatial overlap of kimberlites with ultramafic lamprophyres. The Kuusamo cluster incorporates seven bodies [Kasma 45, Kasma 45 south, Kasma 47, Kalettomanpuro (KP), Kattaisenvaara (KV), Dike 15 and Lampi] distributed along a 60 km NE–SW corridor. Hypabyssal samples from KV, KP, Kasma 45 and Kasma 47 consist of altered olivine macrocrysts and microcrysts and phlogopite phenocrysts in a groundmass of perovskite, apatite, spinel, ilmenite, serpentine, and calcite. These petrographic features combined with mineral (e.g. Mg-rich ilmenite, Al–Ba-rich, Ti–Fe-poor mica) and whole-rock incompatible trace element compositions (La/Nb = 0·8 ± 0·1; Th/Nb = 0·07 ± 0·01; Nb/U = 66 ± 9) are consistent with these rocks being classified as archetypal kimberlites. These Kuusamo kimberlites are enriched in CaO and poor in MgO, which, combined with the absence of chromite and paucity of olivine macrocrysts and mantle-derived xenocrysts (including diamonds), suggests derivation from differentiated magmas after crystal fractionation. Samples from Lampi share similar petrographic features, but contain mica with compositions ranging from kimberlitic (Ba–Al-rich cores) to those more typical of orangeites–lamproites (increasing Si–Fe, decreasing Al–Ti–Ba), and have higher bulk-rock SiO 2 contents than the Kuusamo kimberlites. These features, combined with the occurrence of quartz and titanite in the groundmass, indicate derivation from a kimberlite magma that underwent considerable crustal contamination. This study shows that ...